Leveraging crude extracts from European tree bark to combat oxidative stress, enhance wound healing, and inhibit pathogenic bacterial growth - Sissy Häsler Gunnarsdottir; Johanna Rehrl; Thomas Sepperer; Lena Haretzmüller; David Sesink; Katja Löwenstein; Michael Gadermayr; Claudia Hölzl; Bettina Stelzhammer; Markus Himmelsbach; Gertie Janneke Oostingh; Thomas Schnabel; et al. (Scientific Reports)
Abstract The growing interest in plant-based therapeutics has increased investigations into natural resources rich in bioactive compounds, such as tree bark. Despite historical use in traditional medicine, the therapeutic potential of European tree bark remains underexplored. This study evaluated the antioxidant, antimicrobial, and wound-healing properties of aqueous extracts from the bark of six European tree species, namely Alnus glutinosa, Fagus sylvatica, Betula pendula, Prunus padus, Quercus spp., and Pinus sylvestris. The bark extracts were analyzed for chemical composition, total phenolic content, and antioxidative properties using a DPPH assay and a ROS inhibition assay in human keratinocytes. Antimicrobial activity was tested against seven bacterial strains using a MIC assay, and the wound healing potential was evaluated using a scratch assay. All extracts enhanced wound closure and decreased ROS production in HaCaT cells, with alder and bird cherry bark extracts showing the strongest effects. The antimicrobial assay revealed potent activity against Gram-positive pathogens, with alder bark extract showing the greatest efficacy. The findings highlight the potential therapeutic application of European tree bark extracts in addressing oxidative stress, infections, and wound healing, validating traditional medicinal practices, and providing a sustainable approach for forestry byproducts in modern phytotherapy, potentially contributing to skin disorder treatments.